PANDANGAN FILSAFAT PENDIDIKAN HUMANISME TERHADAP MERDEKA BELAJAR DAN KAMPUS MERDEKA - Raudhotul Jannah; Yeni Erita; Yanti Fitria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
The Minister of Education and Culture's policy on Merdeka Belajar and Merdeka Campus aims to encourage students to master various sciences to enter the world of work. In accordance with Permendikbud Number 3 of 2020 concerning the Merdeka Belajar-Kampus Merdeka Policy regarding the National Higher Education Standards. In the view of humanism, independent learning provides opportunities for students to learn autonomously or independently and take responsibility for themselves. Students have the right to participate in off-campus and off-campus learning in various activities such as student exchanges, internships / work practices, teaching assistance in educational units, research, humanitarian projects, entrepreneurial activities, independent studies / projects, and building villages / Thematic Real Work Lectures (KKNT). The involvement of students in these activities can provide learning experiences (experience learning) as a provision for facing life and life in the future. To realize this learning experience, universities must build cooperation with business / industry and government. Cooperation is based on the framework of improving the professionalism of the academic community. This framework will affect the formulation of the curriculum in determining learning outcomes and the placement of courses outside the university. The quality of learning and the meaningfulness of learning can be achieved by applying humanistic learning principles, namely learning how to learn